OPTIMASI FORMULA KRIM EKSTRAK ETANOL DAUN PATIKAN KEBO (EUPHORBIA HIRTA L.) DENGAN METODE SIMPLEX LATTICE DESIGN - Purwanto, Aris; Amrina, Fina; Riauwati, Rosa (Jurnal Insan Farmasi Indonesia, 2024)
The selection of an emulsifier in a cream formulation is a crucial factor, as the quality and stability of an emulsion. Additionally, an improper ratio of additives can result in unstable physical properties of the product during storage. Patikan kebo (Euphorbia hirta L.) is a plant that can be used as a natural component in anti-aging products. Optimization of 14 cream formulas was carried out using three optimization factors: ethanol extract of patikan kebo leaves (Euphorbia hirta L.) a concentration range of 1-3%, triethanolamine with a concentration range of 2-4%, and stearic acid within a concentration range of 1-3%. The optimization was performed using Design Expert software version 13 used the Simplex Lattice Design (SLD) method. The measured parameters included spreadability, pH, and viscosity. The research results a desirability value of 1.000, with extract ratio of 1%, TEA at 2%, and stearic acid at 3%. This combination resulted in the physical properties of the formulation, including a spreadability of 6.5 ± 0 cm, pH of 5.5 ± 0, and viscosity of 17,880 ± 0.0404 cP, which fulfilled the criteria set by the relevant cream formulation standards.